Comparison of different methods for measuring the superoxide radical by EPR spectroscopy in buffer, cell lysates and cells. (3rd October 2018) - Scheinok, Samantha; Leveque, Philippe; Sonveaux, Pierre; Driesschaert, Benoit; Gallez, Bernard
Abstract: As superoxide anion is of keen interest in biomedical research, it is highly desirable to have a technique allowing its detection sensitively and specifically in biological media. If electron paramagnetic resonance (EPR) techniques and probes have been individually described in the literature, there is actually no comparison of these techniques in the same conditions that may help guiding researchers for selecting the most appropriate approach. The aim of the present study was to compare different EPR strategies in terms of sensitivity and specificity to detect superoxide (vs. hydroxyl radical). Three main classes of EPR probes were used, including paramagnetic superoxide scavengers (such as nitroxides TEMPOL and mitoTEMPO as well as trityl CT-03), a spin trap (DIPPMPO), and diamagnetic superoxide scavengers (such as cyclic hydroxylamines CMH and mitoTEMPO-H). We analysed the reactivity of the different probes in the presence of a constant production of superoxide or hydroxyl radical in buffers and in cell lysates. We also assessed the performances of the different probes to detect superoxide produced by RAW264.7 macrophages stimulated by phorbol 12-myristate 13-acetate. In our conditions and models, we found that nitroxides were not specific for superoxide. CT-03 was specific, but the sensitivity of detection was low. Comparatively, we found that nitrone DIPPMPO and cyclic hydroxylamine CMH were good candidates to sensitively and specifically detect superoxide in complex biological media, CMH offering the best sensitivity.